Negotiating Visuals: Roles of Images in a Site-specific Performance - Muhizam Mustafa; Roslan Chin (Wacana Seni Journal of Arts Discourse, 2019)
Wilkie (2004) in her research "Out of Place" discussed that theatre has a long history of experimenting with a variety of spatial configurations and visual relationships. However, it is only in the last two decades that the label "site-specific" has been applied to theatrical performance, indicating a new mode of place-bound practice. This paper looks at the association between a performative engagement with place and space and the role of visuals and scenography; an enhancement of a site-specific spatial formatted performance. The study also looks at the function of images as one area of the theatrical's "visual systems" that affects the creation and reception of a play. "Bermulanya Di Sini…Kedah Tua" is a contemporary theatrical research project based upon the archaeological findings in Lembah Bujang. The performance combines three different fields of study: performance, archaeology, and history. This research combines the idea of theory and practice to decode literary and historical sources by triangulating the relationship between archaeological artefacts, architectural space and time.